ANALISIS FAKTOR RISIKO STUNTING PADA BALITA DI DESA GLAGAHWANGI KECAMATAN POLANHARJO KABUPATEN KLATEN - Basuki, Prastiwi Putri (STIKES Wira Husada Yogyakarta, 2016)
ABSTRACT The growth of children is one important indicator of the nutritional status of the community. Stunting is the best indicator for the growth of children. The indicators describe the impact of malnutrition and recurrent infections. Stunting is the impact of inadequate child care, poverty, and social and cultural conditions. It is closely related to morbidity and mortality, impaired mental development, reduced intellectual ability, and is a powerful predictor of the development of human resources. This study is observational with cross sectional design. The total sample of 106 people using the exhaustive sampling techniques . The data was collected through interviews and direct observation. The results showed wald test p value